Antisense phosphorodiamidate morpholino oligomers retain activity in Burkholderia cepacia complex biofilm - Mendez, Antonio R.; Pybus, Christine; Greenberg, David E. (Frontiers in Microbiology, 2025)
BackgroundMembers of the Burkholderia cepacia complex (Bcc) are known to cause severe pulmonary infections in immunocompromised hosts, namely individuals with cystic fibrosis (CF) and chronic granulomatous disease (CGD). Due to innate antibiotic-resistant phenotypes and the formation of protective biofilms, Bcc bacteria are difficult to eradicate from colonized lungs using traditional antibiotics. An alternative therapeutic approach involves the use of antisense molecules, specifically peptide-conjugated phosphorodiamidate morpholino oligomers (PPMOs). Previously, we found that PPMOs targeting the acyl carrier protein (AcpP) can reduce the burden of planktonic Bcc bacteria.MethodsAntimicrobial activities of AcpP PPMOs were assessed against established biofilms produced by Bcc clinical isolates, in which viable cells, biomass, and metabolic activity were enumerated. Bactericidal effects were further evaluated by microscopy. Cytotoxicity of these molecules was tested in human pulmonary cell lines.ResultsAcpP PPMO treatment resulted in over three-log reductions (p < 0.0001) in biofilm burden across five clinical isolates of Bcc that were tested. A dose-dependent effect was observed (5–40 μΜ). This effect was visualized using confocal and scanning electron microscopy. We further demonstrated that PPMOs associate with bacterial cells in a time-dependent fashion using a fluorescently labeled AcpP PPMO with B. cenocepacia K56-2 DsRed. Finally, alveolar cells retained viability with AcpP PPMOs at bactericidal dosages.ConclusionThe Bcc biofilm setting is not a deterrent against PPMO delivery or antimicrobial activity. This is supported by the colocalization of AcpP PPMOs with cells, membrane destruction, loss of cell viability, and biomass reduction. Collectively, these data provide evidence that AcpP PPMOs are a promising therapeutic strategy in the treatment of Bcc infections.